TOXIC LIVER DAMAGE IN ACUTE PHASE OF ETHANOL INTOXICATION AND ITS EXPERIMENTAL CORRECTION WITH CHELATE ZINC COMPOUND - A. V. Mashanov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
It was established, that ethanol in the dose of 12 g/kg in experimental animals (white non-inbred male rats) had. expressed damaging effect on the liver, that is shown in statistically significant increase of activity of hepatic enzymes (alanine aminotransferase, alkaline phosphatase), hypoglycemia, development of albuminous and. hydropic degeneration. It is proved, that application of new chelate zinc (2,8,9-trigidrotsinkatrane) in experimental correction of acute ethanol poisoning promotes reduction of metabolic and morphological derangements.